Adolescent Girl Perceptions About Maintaining Mental Health During The COVID-19 Pandemic at Cipta Bhakti Husada Health Vocational School Yogyakarta - Rifka Alya Fatiyyah; Marsiana Wibowo; Khoiriyah Isni (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Adolescents who are a vulnerable group, experience mental health problems during the COVID-19 pandemic. From that, girls experience more mental health problems than boys. The aim of this study was to determine Adolescent girl perceptions about maintaining mental health during the COVID-19 pandemic at SMK Kesehatan Cipta Bhakti Husada Yogyakarta. Methods: This study uses qualitative research with a phenomenological approach. The selection of informants was carried out using a purposive sampling technique with the support of Guidance Counseling teachers in selecting informants. The criteria for this research informant, namely class XI students, female and active in non-academic activities (extra-curricular or organizational). Data collection was carried out by in-depth interview method. Data analysis used in this study is thematic analysis. Results: All informants felt vulnerable and felt serious about mental health problems during the pandemic for various reasons. All informants have the perception that maintaining mental health has benefits and barriers during the pandemic. Cues to take action or stimulus informants to maintain mental health during the COVID-19 pandemic, one of which is from social media in the form of motivation. Health behavior in maintaining mental health from doing hobbies to venting to Allah SWT. Conclusion: It is known that all informants have perceptions of the susceptibility and severity of mental health problems during a pandemic and have perceptions of benefits, barriers and cues to action in maintaining their mental health during the COVID-19 pandemic that can shape their mental health behavior. Schools can carry out mental health promotion programs in the form of education related to mental health.